Identification of engine damages of vintage vehicles with tribological examination - Papp Csenge (University of Belgrade - Faculty of Mechanical Engineering, Belgrade, 2021)
Nowadays, keeping vintage vehicles in operation is becoming more and more popular, however, the reparation of occurring engine malfunctions, and the supply of particulate engine parts mean severe expenses to the owners. In case of older engines, the failure detection is not performed with the help of computerized diagnostics. In several cases the detection of failure is only possible with the disassembly of the engine. A cost-effective solution may be the application of tribological examinations, with which, the malfunctions may be revealed without the needless disassembly of the engine. The purpose of our research is to represent through the tribological examination of a VAZ-2101 (also known as Lada) engine type the practical application of the method, data analysis, evaluation of results and the steps of failure detection.